Preliminary Investigation of Antipyretic Activity of Trinpanchmool Extracts - S Jayalaksmi; Ashoke K Ghosh; Birendra Shrivastava; Rajeev K Singla (International Journal of Phytomedicine, 2011)
Current research work is to evaluate the antipyretic activity of hydroalcoholic extract of trinpanchmool on the wistar rats. Brewer’s yeast induced pyrexia method was used to evaluate febrifuge effect of trinpanchmool extract along with its comparison with its individual constituents on the wistar rats. Darbh, Ikshu and SAR was having better antipyretic activity than the standard drug paracetamol. Combination of the drugs was having better antipyretic that paracetamol but lesser than the individual drugs. Trinpanchmool and its individual drugs are having febrifugatic effect better than our standard paracetamol.